Code talker : a novel about the Navajo Marines of World War Two - Bruchac, Joseph, 1942- (Dial Books, 2005)
After being taught in a boarding school run by whites that Navajo is a useless language, Ned Begay and other Navajo men are recruited by the Marines to become Code Talkers, sending messages during World War II in their native tongue.